Determination of excited singlet-state dipole moments of hydroxy and methoxy coumarins using solvatochromic method - Husain, Mohd Mudassir; Sindhu, Rajeev; Tandon, Harmesh Chander (European Journal of Chemistry, 2012)
The effects of solvents of various polarity on the electronic absorption and fluorescence spectra of 7-hydroxy-4-trifluoromethyl coumarin; 6,7-dihydroxy-4-trifluoromethyl coumarin and 7-methoxy-4-trifluoromethyl coumarin have been investigated. The singlet-state excited dipole moments (μe) and ground state dipole moments (μg) are estimated from Bakshiev and Kawski-Chamma-Viallet equations by using the variation of Stokes’ shift with the solvent’s dielectric constant (ε) and refractive index (n). The observed singlet-state excited dipole moments are found to be larger than the ground-state ones. In addition, the geometry and other electronic properties are computed using ab-initio method with correlation functions at 6-31G basis set.